GPR30-mediated non-classic estrogen pathway in mast cells participates in endometriosis pain via the production of FGF2 - Xu, Xinxin; Wang, Jianzhang; Guo, Xinyue; Chen, Yichen; Ding, Shaojie; Zou, Gen; Zhu, Libo; Li, Tiantian; Zhang, Xinmei (Frontiers in Immunology, 2023)
Pain is one of the main clinical symptoms of endometriosis, but its underlying mechanism is still not clear. Recent studies have shown that the secretory mediators of mast cells activated by estrogen are involved in the pathogenesis of endometriosis-related pain, but how estrogen-induced mast cell mediators are involved in endometriosis-related pain remains unclear. Here, mast cells were found to be increased in the ovarian endometriotic lesions of patients. They were also closely located closely to the nerve fibers in the ovarian endometriotic lesions from of patients with pain symptoms. Moreover, fibroblast growth factor 2 (FGF2)-positive mast cells were upregulated in endometriotic lesions. The concentration of FGF2 in ascites and the protein level of fibroblast growth factor receptor 1 (FGFR1) were higher in patients with endometriosis than in those without endometriosis, and they were correlated with pain symptoms. In vitro, estrogen could promote the secretion of FGF2 through G-protein-coupled estrogen receptor 30 (GPR30) via the MEK/ERK pathway in rodent mast cells. Estrogen-stimulated mast cells enhanced the concentration of FGF2 in endometriotic lesions and aggravated endometriosis-related pain in vivo. Targeted inhibition of the FGF2 receptor significantly restrained the neurite outgrowth and calcium influx in dorsal root ganglion (DRG) cells. Administration of FGFR1 inhibitor remarkably elevated the mechanical pain threshold (MPT) and prolonged the heat source latency (HSL) in a rat model of endometriosis. These results suggested that the up-regulated production of FGF2 by mast cells through non-classic estrogen receptor GPR30 plays a vital role in the pathogenesis of endometriosis-related pain.